Nutrient-acquisition and -utilization strategies of seagrasses in oligotrophic environments - Lin Wu; Jianguo Du; Lingfeng Huang; Hongtao Zhong (Frontiers in Marine Science, 2026)
Seagrass meadows rank among the most productive coastal ecosystems, yet our understanding of their nutrient-acquisition strategies in oligotrophic environments remain fragmented. Current research tends to focus on isolated processes, such as leaf or root uptake, without adequately integrating morpho-physiological traits, sediment heterogeneity, or microbial interactions. This fragmentation constrains our ability to predict seagrass responses to global environmental change. This review synthesizes seagrass nutritional ecology and shows that species in oligotrophic systems employ complementary strategies, including high-affinity foliar absorption, extensive root proliferation, and internal resorption. Crucially, these traits exhibit high plasticity and are modulated by intricate plant-microbe mutualisms, such as nitrogen fixation and phosphorus solubilization. We further demonstrate how sediment properties and hydrodynamic create spatial heterogeneity that dictates site-specific nutrient bioavailability. We propose three priority research directions: (1) deciphering the genetic and epigenetic drivers of phenotypic plasticity adaptation to oligotrophy; (2) applying stable isotope tracers and comparative genomics to quantify the net functional benefits of the seagrass microbiome; and (3) assessing long-term impacts of synergistic stressors (e.g., warming and eutrophication) on meadow structure and biogeochemical functions. By treating oligotrophic environments as natural laboratories, this review informs restoration efforts and the need to safeguard ecosystem services globally, particularly blue carbon sequestration and biodiversity conservation.